Data-Driven Policy Impact Evaluation How Access to Microdata is Transforming Policy Design - Crato, Nuno; Paruolo, Paolo (Springer Nature, 2019)
In the light of better and more detailed administrative databases, this open access book provides statistical tools for evaluating the effects of public policies advocated by governments and public institutions. Experts from academia, national statistics offices and various research centers present modern econometric methods for an efficient data-driven policy evaluation and monitoring, assess the causal effects of policy measures and report on best practices of successful data management and usage. Topics include data confidentiality, data linkage, and national practices in policy areas such as public health, education and employment. It offers scholars as well as practitioners from public administrations, consultancy firms and nongovernmental organizations insights into counterfactual impact evaluation methods and the potential of data-based policy and program evaluation. ; Open Access Demonstrates the potential of data-based policy evaluation Introduces counterfactual impact evaluation methods Includes case studies on policy areas such as public health, education and employment